APLIKASI KEWIBAWAAN DAN KEWIYATAAN DALAM PROSES PEMBELAJARAN SEBAGAI WUJUD PEMAHAMAN GURU TERHADAP HAKEKAT KEMANUSIAAN PESERTA DIDIK - Ida Umami (Postgraduate State Islamic Institute (IAIN) Metro, 2014)
The principles of educational science emphasize the importance of relation between educators and students in high-touch situation. This touch is based on how far educators understand the nature of students as the subject of learners rather than the object of teachers. This understanding and its application by teachers in the learning process in school is presumedly low. The general aim of this study was to get description of teachers’ understanding about the students and its application in learning process. The results of this study revealed that: 1) in general, teachers understanding toward students is in a middle category, and so is with its application toward learning process; 2) five observable variables about the nature of man are valid and can be used to explain teachers’ understanding about the nature of students as latent variable, and six observable variables about high touch are valid and can be used to explain high touch application as application of teachers’ understanding about student in learning process.